FACTORS INFLUENCING E- MARKETING FOR PURCHASE IN ONLINE SHOPPING IN CHENNAI - M. Narmadha; E. Saravanan (International Journal of Engineering Technologies and Management Research, 2025)
Consumer purchase behaviour is a highly pursued area of study within marketing analytics, aimed at comprehending consumer buying behaviours to ultimately augment business revenues and facilitate increased growth rates. In contemporary society, marketing extends beyond basic tools and strategies for promotional reasons; it encompasses a profound comprehension of customer behaviour and the precise anticipation of their subsequent actions. The companies that can foresee with greater accuracy are those driving global market trends and, consequently, are establishing their own trends via enhanced understanding. E-marketing is an optimal domain for readily discerning the effects of various strategies. The research utilises both primary and secondary data, employing methodologies such as factor analysis and correlation to assess its accuracy. This research examines e-marketing elements influencing online purchases in Chennai. A sample of 150 customers evaluating internet shopping in Chennai and their replies to the study-related questions were gathered. This study used a questionnaire as the research instrument. Exploratory Factor Analysis is utilised to ascertain the e-marketing determinants influencing online purchases. Data compilation and analysis are conducted via SPSS v25. The elements influencing e-marketing for online retail purchases in Chennai include perceived usefulness, perceived convenience, perceived enjoyment, information about e-marketing, privacy and security, and website quality.